Epidemiology of Moyamoya Angiopathy in Eastern India - Das, Shambaditya; Dubey, Souvik; Das, Suman; Hazra, Avijit; Pandit, Alak; Ghosh, Ritwik; Ray, Biman Kanti (Frontiers in Neurology, 2022)
INTRODUCTION: Moyamoya Angiopathy(MMA) is a chronic, progressive intracranial vasculopathy with variation in prevalence and clinical manifestations across different populations. This study was aimed to estimate the frequency of MMA as an etiology of stroke and its epidemiological features in the largest cohort of MMA patients in India. METHOD: A single-centered cross-sectional observational study over a period of 5-years(2016-2021) was undertaken among consecutive stroke and transient ischemic attack(TIA) patients to look for presence of MMA angiographically. Each patient with angiographically proven MMA was further evaluated for demographic, clinical and radiological characteristics. RESULTS: Amongst 10,250 consecutive stroke and TIA patients(ischemic-78%,hemorrhagic-22%), frequency of MMA was 1.56%(n=160); 15.3% among children. Female preponderance (Male:Female=1:1.4) was noted amongst 160 MMA patients, with bimodal age-distribution, first peak at 3-8years and shorter second peak at 41-47years. Childhood-onset MMA was seen in 75(46.9%) with commonest initial neurological symptom of fixed-motor-weakness(44.0%), followed by TIA(26.7%); while 85(53.1%) had adult-onset MMA with fixed-motor-weakness(50.6%) followed by headache(24.7%) as the predominant initial neurological symptom; seizure significantly higher in children(p <0.001) and headache in adults(p 0.012). Transient and fixed neurological manifestations constituted 87.5% and 69.4% respectively of symptoms throughout the disease course. Cerebral infarction(45.0%) and TIA(21.9%) were the commonest type of MMA. On brain imaging, infarction was noted in 80.6%; hemorrhage in 11.3%, significantly higher among adults(p <0.001). Cortical infarct and Gyral pattern were commoner in children(p 0.004), subcortical infarcts in adults(p 0.018). Frequent Suzuki staging observed was stage 4(31.3%), followed by stage 3(30.0%). Involvement of posterior circulation was detected in 55.6%, brain atrophy at the time of diagnosis was seen in 65.0%. CONCLUSION: MMA is an important etiological consideration in stroke patients, especially in children. It can present with myriad of transient neurological symptoms, frequently overlooked, leading to delayed diagnosis and contributes to socio-economic burden. Indian MMA showed aberrations in its like gender predisposition, age distribution, frequency of familial cases, disease manifestation and type of stroke, in comparison to its Japanese and Caucasian counterparts pointing to the inter and intra-continent differences of MMA phenotype. Future development of Indian MMA national registry is of essence.